A comparison of cluster and systematic sampling methods for measuring crude mortality - Rose Angela MC; Grais Rebecca F; Coulombier Denis; Ritter Helga (The World Health Organization, 2006)
OBJECTIVE: To compare the results of two different survey sampling techniques (cluster and systematic) used to measure retrospective mortality on the same population at about the same time. METHODS: Immediately following a cluster survey to assess mortality retrospectively in a town in North Darfur, Sudan in 2005, we conducted a systematic survey on the same population and again measured mortality retrospectively. This was only possible because the geographical layout of the town, and the availability of a good previous estimate of the population size and distribution, were conducive to the systematic survey design. RESULTS: Both the cluster and the systematic survey methods gave similar results below the emergency threshold for crude mortality (0.80 versus 0.77 per 10 000/day, respectively). The results for mortality in children under 5 years old (U5MR) were different (1.16 versus 0.71 per 10 000/day), although this difference was not statistically significant. The 95% confidence intervals were wider in each case for the cluster survey, especially for the U5MR (0.15-2.18 for the cluster versus 0.09-1.33 for the systematic survey). CONCLUSION: Both methods gave similar age and sex distributions. The systematic survey, however, allowed for an estimate of the town's population size, and a smaller sample could have been used. This study was conducted in a purely operational, rather than a research context. A research study into alternative methods for measuring retrospective mortality in areas with mortality significantly above the emergency threshold is needed, and is planned for 2006.